# 7 + 5(x-2) = 3(5x+1) -12 how to solve for x?

### 6 Answers | Add Yours

7 + 5(x-2) = 3(5x+1) -12

First let us open brackets:

==> 7 + 5x - 10 = 15x +3 -12

Simplify:

==> 5x -3 = 15x - 9

Now group similar terms:

==> 10x = 6

Now divide by 10:

==> x = 10/6= 5/3

Then the solution is x= 5/3

7+5(x-2) = 3(5x+1)-12 solve for x

1. First we would have to multiply the numbers in the parentheses by the number that is outside of it. 7 + 5x - 10 = 15x + 3 - 12

2. Then, add all like terms. 5x - 3 = 15x - 9

3. Now, we want all of the x's to one side and the integers to the other side. So we subtract 5x from both sides and add 9 to both sides. 6 = 10x

4. Finally, we divide 10 from both sides to get the x alone. 6/10 = x

5. Simplify 3/5 = x

6. Now we know that x = 3/5 or .60

7 + 5(x-2) = 3(5x+1) -12 First you are going to have to multiply the term that is outside the parentheses on both sides of the equation with the terms inside the parentheses.

7 + 5x - 10 = 15x + 3 -12 Now combine like terms on both sides.

5x - 3 = 15x - 9 Now add 9 on both sides

(5x - 3) +9 = (15x - 9) +9

5x + 6 = 15x Now subtract 5x from both sides

(5x + 6) -5x = (15x) - 5x

6/10 = 10x/10 then divide 10 on both sides of the equation to get the x by itself.

x = 3/5 = 0.60

We'll move all terms of the given equality to one side.

7 + 5(x-2) - 3(5x+1) +12 = 0

Now, we'll remove the brackets:

7 + 5x - 10 - 15x - 3 + 12 = 0

We'll combine like terms:

-10x + 6 = 0

We'll subtract 6 both sides:

-10x = -6

We'll divide by -10 both sides:

x = -6/-10

**x = 3/5**

**or**

**x = 0.6**

7+5(x-2) = 3(5x+1)-12. To solve for x:

Solution:

OPen the bracket:

7+5x-5*2 = 15x+3-12.

Simplify both sides.

5x-3 = 15x-9. subtract 15x - 3 from both sides to collect x's on left and numbers on right.

5x-15x = -9+3

-10x = -6

-10x/-10 = -6/-10

x =0.6

Given:

7 + 5(x - 2) = 3(5x + 1) - 12

==> 7 + 5x - 10 = 15x + 3 - 12

Transferring all containing x on left hand side and other terms on right hand side:

==> 5x - 15x = 3 - 12 - 7 + 10

==> - 10x = - 6

Dividing both sides by -10

x = 6/10 = 3/5

Answer:

x = 3/5